Macoilin, a conserved nervous system-specific ER membrane protein that regulates neuronal excitability. - Fausto Arellano-Carbajal; Luis Briseño-Roa; Africa Couto; Benny H H Cheung; Michel Labouesse; Mario de Bono (PLoS Genetics)
Genome sequence comparisons have highlighted many novel gene families that are conserved across animal phyla but whose biological function is unknown. Here, we functionally characterize a member of one such family, the macoilins. Macoilins are characterized by several highly conserved predicted transmembrane domains towards the N-terminus and by coiled-coil regions C-terminally. They are found throughout Eumetazoa but not in other organisms. Mutants for the single Caenorhabditis elegans macoilin, maco-1, exhibit a constellation of behavioral phenotypes, including defects in aggregation, O₂ responses, and swimming. MACO-1 protein is expressed broadly and specifically in the nervous system and localizes to the rough endoplasmic reticulum; it is excluded from dendrites and axons. Apart from subtle synapse defects, nervous system development appears wild-type in maco-1 mutants. However, maco-1 animals are resistant to the cholinesterase inhibitor aldicarb and sensitive to levamisole, suggesting pre-synaptic defects. Using in vivo imaging, we show that macoilin is required to evoke Ca²(+) transients, at least in some neurons: in maco-1 mutants the O₂-sensing neuron PQR is unable to generate a Ca²(+) response to a rise in O₂. By genetically disrupting neurotransmission, we show that pre-synaptic input is not necessary for PQR to respond to O₂, indicating that the response is mediated by cell-intrinsic sensory transduction and amplification. Disrupting the sodium leak channels NCA-1/NCA-2, or the N-,P/Q,R-type voltage-gated Ca²(+) channels, also fails to disrupt Ca²(+) responses in the PQR cell body to O₂ stimuli. By contrast, mutations in egl-19, which encodes the only Caenorhabditis elegans L-type voltage-gated Ca²(+) channel α1 subunit, recapitulate the Ca²(+) response defect we see in maco-1 mutants, although we do not see defects in localization of EGL-19. Together, our data suggest that macoilin acts in the ER to regulate assembly or traffic of ion channels or ion channel regulators.